Komunikasi Interpersonal dalam Peningkatan Kinerja ASN BKPSDM Kabupaten Banyumas - Anggit Pamungkas; Khusnul Khotimah (ARKANA: Jurnal Komunikasi dan Media, 2022)
The existence of human resources plays a very important role in an agency. Employees as motivated human resources will carry out an activity or task as well as possible so as to provide maximum work results. In an organization or agency communication activities is one very important activity. Communication that exists between individuals in an organization is interpersonal communication. Interpersonal communication as the most basic form of communication in an organization, if its intensity is maintained, will have a positive impact on the organization, especially superiors and subordinates. The method in this research is qualitative with a descriptive approach. Interpersonal communication at BKPSDM Banyumas Regency creates good relationships between one BKPSDM employee and another. This relationship has an impact on the emergence of an attitude of openness and trust obtained from interpersonal relations in the BKPSDM work environment. The performance of an employee will increase if there is a suitability of high work ability. Interpersonal communication is a very practical art, useful in establishing relationships with business partners, colleagues, including at the managerial level that requires interpersonal communication. In practice, good interpersonal communication will also create good employee performance because the work environment is able to support optimal work